The Postcolonial Galaxy or a Galactic Postcoloniality: - Subhayu Bhattacharjee (Sanglap: Journal of Literary and Cultural Inquiry, 2021)
The Foucauldian notion of the “productive” component of power manifested in the semblance of autonomy in “transparent” subjects unsettles Francis Fukuyama’s aspirations about information technology that breaks the “monopoly over information.”  Knowledge of the colonial subject in the Foucauldian paradigm and its indispensable role in the manifestation of colonial power have been the mainstay of postcolonial phenomenological reflections of the Self/Other. The Foucauldian notion of the subject’s delusional agency in liberal discourses, however, witnesses a further modification in fiction speculating on Artificial Intelligence. This results in the rupture of complacency about authoritarian control, since Artificial Intelligence, as an offshoot of the revolution so dear to Fukuyma, produces the case for a new kind of subject in speculative fiction like Asimov’s The Naked Sun. What emerges subsequently is the example of an intelligent subject capable not simply of producing knowledge but also withholding it— a simulated intelligence that is human-but-not-quite. This gives rise to an anxiety of control experienced by the human subject like the detective Baley in Asimov’s text who wishes to make the robot-assistant, Daneel, serve his purpose only. Such an anxiety experienced in the face of the rupture of projection of the purpose of robotics research mimics postcolonial anxieties in the event of rupture of colonial projections on the Other. This paper seeks to explore postcolonialism as a condition not only reflective of the past but also an expedient tool to measure anxieties, fantasies, and their subsequent sublimation in speculative fiction on the future of robotics and Artificial Intelligence, as in Asimov’s text.